Semiotics Integration in Understanding Story on Al Qur’an (Applying Narrative Theory of A.J Greimas towards the Story of the People of the Garden on QS. Al Qalam 17-32) - Muhammad Alwi HS; Iin Parninsih (Institut Agama Islam Negeri Salatiga, 2021)
Aiming to discuss the reading of semiotics in revealing the understanding story on Al Qur’an, this paper applies the narrative theory by A.J. Greimas on the story of the people of the Garden on QS. Al Qalam 17-32. This paper discusses the story due to the lack of research discussing about it, not limited to semiotics study. In fact, the story contains moral values that need to be elaborated. Therefore, starting from the assumption that the Qur'an through the story of the people of the garden has a moral ideal mission for mankind– especially Muslims, including both understanding within themselves and departing from outside scholar, this paper aims to prove the importance of the presence of stories in Al Qur'an through the integration of science outside Islam, namely semiotics. This research intends to answer the question on how to understand the narrative and moral ideals in the story of the garden owner in QS. Al-Qalam: 17-32 based on the narrative theory of A.J. Greimas.